Riboflavin-mediated RDX transformation in the presence of Shewanella putrefaciens CN32 and lepidocrocite - Bae, Sungjun; Lee, Yoonhwa; Kwon, Man Jae; Lee, Woojin (ELSEVIER SCIENCE BV, 2014)
The potential of riboflavin for the reductive degradation of a cyclic nitramine, hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX), was investigated in the presence of lepidocrocite and/or Shewanella putrefaciens CN32. RDX reduction by CN32 alone or CN32 with lepidocrocite was insignificant, while 110 mu M RDX was completely reduced by CN32 with riboflavin in 78 h. The transformation products identified included nitroso metabolites, formaldehyde, and ammonium, indicating the ring cleavage of RDX. UV and visible light analysis revealed that riboflavin was microbially reduced by CN32, and that the reduced riboflavin was linked to the complete degradation of RDX. In the presence of both CN32 and lepidocrocite (gamma-FeOOH), 100 mu M-riboflavin increased the rate and extent of Fe(II) production as well as RDX reduction. An abiotic study also showed that Fe(II)-riboflavin complex, and Fe(II) adsorbed on lepidocrocite, reduced RDX by 48% and 21%, respectively. The findings in this study suggest that riboflavin-mediated RDX degradation pathways in subsurface environments are diverse and complex. However, riboflavin, either from bacteria or exogenous sources, can significantly increase RDX degradation. This will provide a sustainable clean-up option for explosive-contaminated subsurface environments. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: EXTRACELLULAR ELECTRON-TRANSFER; HEXAHYDRO-1,3,5-TRINITRO-1,3,5-TRIAZINE RDX; ABIOTIC TRANSFORMATION; CARBON-TETRACHLORIDE; ONEIDENSIS MR-1; ZEROVALENT IRON; BIODEGRADATION; DEGRADATION; ANTHRAQUINONE-2,6-DISULFONATE; BIOTRANSFORMATION